At the Margins of Identity: Human-Animal Relations in the Parallel Stories of Péter Nádas - Darabos, Enikő (Margins/Marges/Margini, 2025)
This paper explores the intersection of literature and Human-Animal Studies (HAS) through Péter Nádas’s novel, Parallel Stories [Párhuzamos történetek]. It examines how the work challenges traditional notions of identity and otherness, particularly in human-animal relationships. Drawing on HAS’s interdisciplinary approach, which critiques anthropocentric perspectives, the study analyses how Nádas’s narrative through the Jonesian “performativities of bodies” blurs boundaries between humans and animals. Theoretical frameworks from Jacques Derrida and Donna Haraway inform the analysis, particularly Derrida’s concept of “the other” and Haraway’s posthumanist thought on human-animal entanglements. Focusing on Kristóf’s encounter with a black dog in Budapest’s hidden gay scene at the Margaret Island, the paper provides insight into the secret gay cruising subculture of the time. This relationship highlights shared experiences of marginality and otherness, uniting humans and animals as outsiders in their social contexts. Nádas’s intense focus on corporeal experiences offers a profound meditation on human existence, reconciling conflicting aspects of flesh and spirit, instinct and reason. By examining Nádas’s portrayal of raw animality in human nature, the study contributes to literature on posthumanism and animal studies in contemporary fiction. Through this analysis, the paper demonstrates how literary works can expand our understanding of humanity in relation to the animal world, reinterpreting concepts of identity and otherness. By engaging with HAS and deconstructive theories, the study offers new insights into how narratives like Parallel Stories challenge and refine our perceptions of human-animal relationships.